Factors influencing the hesitancy and refusal of vaccines in India: A study-using tool developed by WHO SAGE Working Group - Bilal Moosa, Mohamed; Josh, Devayani; Bobby, Reshma; Biju, Besty; Sebastian, Juny; Baby John, Sheba; Dhati Ravi, Mandyam (Trends in Immunotherapy, 2024)
Objectives: This study aimed to assess the hesitancy towards vaccination and to identify the factors and predictor variables within the study population. Methodology: This was a cross-sectional study conducted via a web-based platform where a validated questionnaire was circulated among the public to understand their hesitancy towards vaccination. WHO SAGE Working Group Questionnaire was used to collect the data. The predictors for hesitancy were determined by using bivariate logistic regression analysis and the prevalence of vaccine hesitancy was identified. Results: A total of 353 subjects enrolled in the study during the 6 months of the study. Among them, 133 (37.67%) subjects showed vaccine hesitancy. On performing the bi-variate analysis, it was found that among the subsets studies those who were more hesitant to receive vaccines were females (OR: 1.476); individuals who are widowed/separated/divorced (OR: 3.109), age 40–49 yrs (OR: 3.710); from a rural (OR: 1.277) and not graduated (OR: 1.077). These subsets were predictors identified for vaccine hesitancy. Among the vaccines, maximum hesitancy was observed for the chicken pox vaccine [47 (13.31%)], followed by TCV [25 (7.08%)] and Rota [24 (6.79%), whereas the minimum hesitancy was observed for BCG [2 (0.56%)], OPV [4 (1.13%)] and IPV [8 (2.26%)]. Reasons provided for the hesitancy observed were mainly (i) Did not think it was needed [163 (46.17%)], (ii) Did not think the vaccine was safe [41 (11.61%)] and (iii) Did not know where to get vaccinated [24 (6.79%)]. Conclusion: The study observed less vaccine hesitancy among vaccines included in the EPI program. A major contributing factor for VH among the study population was their wrong perception about vaccines as that is not needed and not safe. Hence, there is a real need for education to the population to improve vaccine confidence among the general population.